2010
DOI: 10.1111/j.1530-0277.2010.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Metabolic Pathways of Ethanol Responsible for Oxidative DNA Damage in Human Peripheral Lymphocytes

Abstract: This study provides direct evidence that ethanol can induce oxidative DNA damage in human peripheral lymphocytes in vitro, and its mechanism may be associated with the metabolism of ethanol by the ADH1B/ALDH2 pathway. Moreover, ethanol-induced DNA damage can be auto-repaired by human peripheral lymphocytes possibly mediated by the BER system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
79
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 36 publications
16
79
2
Order By: Relevance
“…Our finding that DLMO by Method 1 was correlated with amount of drinking prior to the study suggests that perhaps there is a direct pathophysiological link between alcohol and circadian function, extending preclinical studies in mice that showed that forced ethanol consumption affects circadian activity in a dose-dependent manner (Brager et al 2010, 2011). Brager et al 2011 also found that acute alcohol consumption inhibits the phase resetting response of the mouse circadian clock to non-photic (serotonergic) phase resetting properties.…”
Section: Discussionsupporting
confidence: 70%
“…Our finding that DLMO by Method 1 was correlated with amount of drinking prior to the study suggests that perhaps there is a direct pathophysiological link between alcohol and circadian function, extending preclinical studies in mice that showed that forced ethanol consumption affects circadian activity in a dose-dependent manner (Brager et al 2010, 2011). Brager et al 2011 also found that acute alcohol consumption inhibits the phase resetting response of the mouse circadian clock to non-photic (serotonergic) phase resetting properties.…”
Section: Discussionsupporting
confidence: 70%
“…The cells were treated with 160 μM CoCl 2 for different times (15,30,60,120,180 and 360 min), then lysed with cold lysis buffer as described previously [24]. Cell lysate were electrophoresed on a 10% SDSPAGE gel, and transferred onto polyvinylidene difluoride membranes (Millipore Corporation, Bedford, MA).…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…This shows an efficient repair mechanism of damaged DNA [55]. Further, it was found that DNA damage and intracellular 8-oxoguanine levels induced by ethanol can be 'auto-repaired' in human peripheral lymphocytes during a recovery phase [56]. It may be speculated that similar repair mechanisms are available in Caco-2 cells.…”
Section: Caco-2 Cellsmentioning
confidence: 95%